Innovation of Lebay Chips (Catfish And Spinach) in the Gunung Anyar Tambak Chip’s Village Surabaya - Nuruni Ika Kusuma Wardani; Mei Retno Adiwaty; Ignatia Martha Hendrati (Nusantara Science and Technology Proceedings)
Lebay Crackers (Catfish and Spinach Calcium) have a high nutritional content, this cracker is made from natural ingredients of the combination of catfish with spinach vegetables. Utilization of Science and Technology for Society (PIKAT) needs to be implemented with the intention to transfer appropriate technology especially in the field of processing of fishery with spinach vegetable Type of processed catfish that will be developed is Lupil Cracker mixed with Spinach Spinach (Lebay Crackers). The development of processed business Catfish chips Blended with spinach vegetables (Lebay Crackers) is in addition to potential as a profitable business, on the other hand, can also give a more positive impact for the economic improvement of surrounding communities. First, Lebay Kerupuk processed business opens job opportunities for Ibu Inayah and the community. With the existence of dough cracker processing machine that has technology reliability, simple shape, easy to operate, and can increase the quantity and quality of production and make packaging.